Susceptibility of zoysiagrass germplasm to large patch caused by Rhizoctonia solani - Obasa, Ken C.; Fry, Jack D.; Kennelly, Megan M. (My University, 2012)
Fourteen new zoysiagrass (Zoysia spp.) germplasm lines from parental crosses including Z. japonica (Steud.), Z. matrella (L.) Merr., and Z. pacifica (Goudswaard) were evaluated for susceptibility to large patch caused by the fungus Rhizoctonia solani Kühn anastomosis group (AG) 2-2 LP. The germplasm lines were compared with ‘Meyer’ (Zoysia japonica Steud.), the most widely used cultivar in the transition zone of the United States, under growth chamber and field conditions. Large patch susceptibility in the growth chamber study was estimated five days post-inoculation and thereafter for 25 days. Three pots of each line and ‘Meyer’ were randomly selected and rated for disease incidence by determining the percentage of individual shoots in each pot with distinct, water-soaked brown lesions on the leaf sheath. Field assessment of large patch susceptibility was carried out weekly and was by direct measurement of patch sizes as well as by digital image analysis of plots for the percentage of diseased turf. All 14 progeny had similar disease levels compared with ‘Meyer’ in the growth chamber, but only six consistently had disease levels as low as ‘Meyer’ in the field. Growth chamber results did not correlate to field results.
Citation: Obasa, K., Fry, J., Kennelly, M. (2012). Susceptibility of Zoysiagrass Germplasm to Large Patch Caused by Rhizoctonia solani. HortScience, 47(9), 1252–1256. https://doi.org/10.21273/HORTSCI.47.9.1252
Keywords: Turfgrass pathology; Fungal disease; Transition zone; Disease management; Digital image analysis; Zoysiagrass; Rhizoctonia solani